2015
DOI: 10.1088/2041-8205/814/1/l6
|View full text |Cite
|
Sign up to set email alerts
|

C Iii] Emission in Star-Forming Galaxies Near and Far

Abstract: We measure [C III] 1907, C III] 1909 Å emission lines in 11 gravitationally lensed star-forming galaxies at z ∼ 1.6-3, finding much lower equivalent widths than previously reported for fainter lensed galaxies. While it is not yet clear what causes some galaxies to be strong C III] emitters, C III] emission is not a universal property of distant star-forming galaxies. We also examine C III] emission in 46 star-forming galaxies in the local universe, using archival spectra from GHRS, FOS, and STIS on HST and IU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
150
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(173 citation statements)
references
References 44 publications
21
150
2
Order By: Relevance
“…Based on the correlation in strength between C iii] and Mg ii emission (Section 4.3), this result suggests indirectly that stronger C iii] may be found within lower-metallicity galaxies in our sample. Our inferred correlation between C iii] and metallicity is not only consistent with both models and observations of C iii] at other redshifts Rigby et al 2015;Jaskot & Ravindranath 2016), but is also supported by the result that CIII] emission is significantly stronger in the lower-mass half of our sample, given the well-measured correlation between metallicity and stellar mass (e.g., Tremonti et al 2004;Zahid et al 2013). …”
Section: Iii] Vs Metallicitiessupporting
confidence: 89%
See 2 more Smart Citations
“…Based on the correlation in strength between C iii] and Mg ii emission (Section 4.3), this result suggests indirectly that stronger C iii] may be found within lower-metallicity galaxies in our sample. Our inferred correlation between C iii] and metallicity is not only consistent with both models and observations of C iii] at other redshifts Rigby et al 2015;Jaskot & Ravindranath 2016), but is also supported by the result that CIII] emission is significantly stronger in the lower-mass half of our sample, given the well-measured correlation between metallicity and stellar mass (e.g., Tremonti et al 2004;Zahid et al 2013). …”
Section: Iii] Vs Metallicitiessupporting
confidence: 89%
“…Photoionization models and observations at different redshifts have revealed that low gas metallicity leads to enhanced nebular C iii] emission due to the hard ionizing SED of the associated metal-poor stars exciting the gas, and the elevated electron temperature resulting from reduced metal cooling (e.g., Erb et al 2010;Stark et al 2014;Rigby et al 2015;Jaskot & Ravindranath 2016, see Section 5.2.2 for a detailed discussion). In order to examine if the correspondence between C iii] emission and metallicity found in high-redshift studies also holds for z ∼ 1, we estimated metallicities using optical emission features.…”
Section: Iii] Vs Metallicitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Si II) absorption lines from neutral outflowing gas and high-ionization features such as a strong P Cygni stellar wind profile of C IV, which is indicative of stellar winds from very young and massive stars. The observed C III] λλ1907, 1909 Å emission, W r (C III]) = −6 ± 4 Å, is also indicative of an intense burst of star formation that is coupled with low metallicity (Bayliss et al 2014;Rigby et al 2015).…”
Section: Spectroscopymentioning
confidence: 89%
“…The C iii] equivalent width of 7.1Å is very similar to the value of 7.7Å that we measure for the FOS spectrum near cluster #5. Rigby et al (2015) discuss measurements of C iii] emission in nearby and high redshift galaxies. In their nearby sample, they include the FOS spectrum of NGC 5253 used here, and note that this galaxy is one of the 20% of local galaxies that show strong C iii] emission.…”
Section: Comparison With He Ii-emitting High Redshiftmentioning
confidence: 97%